Решите выражение с объяснением!!!!!! (√27-2)(2-3√3)
Решите выражение с объяснением!!!!!!
(√27-2)(2-3√3)
Ответ(ы) на вопрос:
Гость
[latex](\sqrt{27}-2)(2-3\sqrt3)=(\sqrt{3^2\bullet3}-2)(2-3\sqrt3)=\\\\=(3\sqrt{3}-2)(2-3\sqrt3)=(-2+3\sqrt{3})(2-3\sqrt3)=\\\\=(-(2-3\sqrt{3}))(2-3\sqrt3)=-(2-3\sqrt{3})(2-3\sqrt3)=\\\\=-(2-3\sqrt3)^2=-(2^2-2\bullet2\bullet3\sqrt3+(3\sqrt3)^2)=\\\\=-(4-12\sqrt3+3^2(\sqrt3)^2)=-(4-12\sqrt3+9\bullet3)=\\\\=-(4-12\sqrt3+27)=-4+12\sqrt3-27=12\sqrt3-31.[/latex]
Не нашли ответ?
Похожие вопросы